Social media use in adolescents and young adults with serious illnesses: an integrative review. Issue 3 (4th December 2018) - Peat, George; Rodriguez, Alison; Smith, Joanna
Abstract : Objectives: Adolescents and young adults with life-limiting or life-threatening conditions are often socially isolated because of the demands of their illness. Although adolescents and young adults have a noticeable online and social media presence, their motivations for using social media remain unclear. This article aims to summarise empirical research undertaken about how and why social media is used by adolescents and young adults with life-limiting or life-threatening conditions. Methods: An integrative literature review was undertaken. Key healthcare research databases including CINHAL, MEDLINE and PSYCHINFO were searched for empirical studies reporting the use of social media by adolescents and young adults with life-limiting or life-threatening conditions. Fifteen articles met the inclusion criteria; included articles were quality appraised and a thematic synthesis undertaken to identify key themes. Results: The reasons why adolescents and young adults with life-limiting or life-threatening conditions use social media are diverse, with differences relating to age and gender. However, this population in general uses social media to connect with others who have similar lived experiences. Conclusion: Social media platforms can be useful adjuncts to the care of adolescents and young adults with life-limiting or life-threatening conditions. However, current evidence is dominated by studies on social media use by adolescents and young adults with cancer. More research is required to gain a holistic understanding of how and why social media is used by this population and its perceived benefits and limitations.